Supply chain management : strategy, planning, and operation - Chopra, Sunil , 1960-; Meindl, Peter , 1970- (Pearson, 2013)
Illustrating the key drivers in effective supply chain management. "Supply Chain Management" illustrates the key drivers of good supply chain management in order to help readers understand what creates a competitive advantage. The fifth edition continues to increase the focus on global supply chain